The Therapeutic Potential of the Essential Oil of Thymbra capitata (L.) Cav., Origanum dictamnus L. and Salvia fruticosa Mill. And a Case of Plant-Based Pharmaceutical Development - Pirintsos, S. A.; Bariotakis, M.; Kampa, M.; Sourvinos, G.; Lionis, C.; Castanas, E. (Frontiers in Pharmacology, 2020)
This review performs a comprehensive assessment of the therapeutic potential of three native herbs of Crete (Thymbra capitata (L.) Cav., Salvia fruticosa Mill. and Origanum dictamnus L.), their phytochemical constituents, health benefits and issues relevant to their safety, within a translational context. Issues discussed comprise: (1) Ethnopharmacological uses of the three herbs, reviewed through an extensive search of the literature; (2) Systematic analysis of the major phytochemical constituents of each plant, and their medicinal properties; (3) To what extent could the existing medicinal properties be combined and produce an additive or synergistic effect; (4) Possible safety issues. We conclude with a specific example of the use of a combination of the essential oils of these plants as an effective anti-viral product and the experience gained in a case of a plant-based pharmaceutical development, by presenting the major steps and the continuum of the translational chain.